2017
DOI: 10.1002/ejic.201700920
|View full text |Cite
|
Sign up to set email alerts
|

Cyanido‐Bridged FeII–MI Dimetallic Hofmann‐Like Spin‐Crossover Coordination Polymers Based on 2,6‐Naphthyridine

Abstract: Abstract:Two new 3D spin-crossover (SCO) Hofmann-type coordination polymers {Fe (2,6-naphthy) -linkers define wide rectangular windows that favor the interpenetration of three identical 3D networks, strong

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Enthalpy and entropy changes associated to the phase transition were obtained by integrating the excess heat capacity (after subtraction of the lattice contribution) over T and ln T , respectively. The calculated values (Δ H =−14.3 KJ mol −1 and Δ S =−52.8 JK −1 mol −1 ) compare well with those reported for other related complexes showing also very abrupt spin crossover and strong cooperativity [38–42] . The entropy change is much higher than the sum of the electronic part ( R ln5≈13.4 JK −1 mol −1 ) and the expected vibronic contribution based on the change of Fe−N distances.…”
Section: Resultssupporting
confidence: 85%
“…Enthalpy and entropy changes associated to the phase transition were obtained by integrating the excess heat capacity (after subtraction of the lattice contribution) over T and ln T , respectively. The calculated values (Δ H =−14.3 KJ mol −1 and Δ S =−52.8 JK −1 mol −1 ) compare well with those reported for other related complexes showing also very abrupt spin crossover and strong cooperativity [38–42] . The entropy change is much higher than the sum of the electronic part ( R ln5≈13.4 JK −1 mol −1 ) and the expected vibronic contribution based on the change of Fe−N distances.…”
Section: Resultssupporting
confidence: 85%
“…It is concluded that the weak interlayer contacts 2). [83] The densely packed 1 exhibited a relatively abrupt two-step SCO in the temperature interval 150-215 K, whereas 2, with nitrobenzene as guest molecules, featured an incomplete one-step SCO behavior (T 1/2 = 166 K) that extended over 150 K.…”
Section: Chemical Compositional Modulationsmentioning
confidence: 98%
“…discovered an in situ generated elongated [Ag 2 (CN) 3 ] − linker in a triply interpenetrated framework {Fe(2,6‐naphthy)[Ag(CN) 2 ][Ag 2 (CN) 3 ]} (2,6‐naphthy = 2,6‐naphthyridine) (1) compared to the prototypical doubly interpenetrated {Fe(2,6‐naphthy)[Au(CN) 2 ] 2 }·0.5PhNO 2 (2). [ 83 ] The densely packed 1 exhibited a relatively abrupt two‐step SCO in the temperature interval 150–215 K, whereas 2, with nitrobenzene as guest molecules, featured an incomplete one‐step SCO behavior ( T 1/2 = 166 K) that extended over 150 K.…”
Section: Applications Of Cyanide‐based Porous Materialsmentioning
confidence: 99%
“…In recent years, some examples by using the [Ag 2 (CN) 3 ] − unit were reported. 8 Although an isostructural series of Fe II (L) 2 [Au(CN) 2 ] 2 and Fe II (L) 2 [Ag(CN) 2 ] 2 have been much reported, the [Au 2 (CN) 3 ] − unit is still not found. Thus, the [Ag 2 (CN) 3 ] species is a rare building unit.…”
Section: Introductionmentioning
confidence: 99%